TINJAUAN YURIDIS TERHADAP PERLINDUNGAN WARTAWAN DALAM PENGUNGKAPAN IDENTITAS NARASUMBER PELAKU MATCH FIXING - Hans Poliman; Adityo Saputra; Windisen Windisen (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Sport is one of the priorities in advancing development at the national level, so that the field of sports has a very large role as an effort to make the name of the nation and state proud and promote national development, so that regulations regarding sports in the national legal system must be accountable, football has ranked first as a sport. However, the public's enthusiasm for football is not matched by the quality provided by the federation, namely the All-Indonesian Football Association (PSSI) in building a modern football industry and with integrity, one of the problems that has occurred from the past until now is match fixing. which is currently being hotly discussed on one of the television programs, namely the mata najwa program which has a topic entitled